Association of TLR7 rs864058 Genotypic Variation and mRNA Expression with COVID-19 Severity and Clinical Outcomes: TLR7 rs864058 Genotypic Variation and mRNA Expression with COVID-19 - Khalid, Beenish; Baig, Saeeda; Angelo, Shian; Riaz, Misbah; Rathore, Padma; Perveen, Fauzia (Pakistan Journal of Health Sciences, 2025)
Genetic variations in TLR7 could modulate the severity of COVID-19. Objectives: To find the association between TLR7 mRNA expression, genotypic variations, and disease severity in COVID-19 patients. Methods: A cross-sectional observational study was conducted on 59 PCR-confirmed COVID-19 patients at Ziauddin Hospital, Karachi (June 2022–May 2023). Blood samples were analyzed for TLR7 genotyping via PCR and Sanger sequencing. Disease severity was classified into three groups based on clinical guidelines. TLR7 mRNA expression was quantified using real-time PCR (qPCR), and hospitalization, ICU admission, and complications were documented. Results: Higher TLR7 mRNA expression was observed in patients with the GG genotype compared to those with the GA genotype (p=0.04). Individuals carrying the GG genotype exhibited greater hospitalization rates (75.5% vs. 40%, p=0.009), increased ICU admission (28.6% vs. 10%, p=0.041), and a higher need for mechanical ventilation (20.4% vs. 10%, p=0.049). Respiratory failure occurred more often in the GG genotype group (20.4% vs. 10%, p=0.038). Conclusions: It was concluded that the GG genotype of TLR7 was related to higher susceptibility to severe COVID-19 outcomes, with higher hospitalization rates, ICU admission, and respiratory failure.